Die verhouding tussen kerk en ??á?? in Pauliniese perspektief - J. A. du Rand (Acta Theologica)
The aim of this contribution is to investigate the pivotal semantic position taken by ??á?? in its relationship to the Pauline concept of church. ??á?? is a kó?os a strenuous labour (1 Thess. 1:3), not to be considered a means or strategy to achieve something but to characterise the typical depicted eschatological character of the Pauline ????????. Selected aspects of ??á?? in 1 Thessalonians, 1 and 2 Corinthians, Romans, Galatians and Ephesians are investigated to illustrate the remarkable relationship between ???????? and ??á??.